#1**+15 **

We have that either,

l x -1 l - 5 = 6 or that (l x -1 l - 5) = - 6

Working with the first, we have

l x - 1 l = 11 which implies that

x - 1 = 11 and x - 1 = -11

So x = 12 and x = -10

And working with the second, we have

l x - 1 l - 5 = -6

l x - 1 l = -1 which is impossible

So, the sum of the roots = 2

CPhill
Feb 8, 2015

#1**+15 **

Best Answer

We have that either,

l x -1 l - 5 = 6 or that (l x -1 l - 5) = - 6

Working with the first, we have

l x - 1 l = 11 which implies that

x - 1 = 11 and x - 1 = -11

So x = 12 and x = -10

And working with the second, we have

l x - 1 l - 5 = -6

l x - 1 l = -1 which is impossible

So, the sum of the roots = 2

CPhill
Feb 8, 2015